Biochemical analyses of a novel acidophilic GH5 β-mannanase from Trichoderma asperellum ND-1 and its application in mannooligosaccharides production from galactomannans - Zheng, Fengzhen; Basit, Abdul; Wang, Jiaqiang; Zhuang, Huan; Chen, Jun; Zhang, Jianfen (Frontiers in Microbiology, 2023)
In this study, a acidophilic GH5 β-mannanase (TaMan5) from Trichoderma asperellum ND-1 was efficiently expressed in Pichia pastoris (a 2.0-fold increase, 67.5 ± 1.95 U/mL). TaMan5 displayed the highest specificity towards locust bean gum (Km = 1.34 mg/mL, Vmax = 749.14 μmol/min/mg) at pH 4.0 and 65°C. Furthermore, TaMan5 displayed remarkable tolerance to acidic environment, retaining over 80% of its original activity at pH 3.0-5.0. The activity of TaMan5 was remarkably decreased by Cu2+、Mn2+ and SDS, while Fe2+/Fe3+ improved the enzyme activity. TLC analysis of action model showed that TaMan5 could rapidly degrade mannan/MOS into mannobiose without mannose via hydrolysis action as well as transglycosylation. Site-directed mutagenesis results suggested that Glu205, Glu313 and Asp357 of TaMan5 are crucial catalytic residues, with Asp152 playing an auxiliary function. Additionally, TaMan5 and commercial α-galactosidase displayed a remarkable synergistic effect on the degradation of galactomannans. This study provided a novel β-mannanase with ideal characteristics and can be considered a potential candidate for the production of bioactive polysaccharide mannobiose.